Boost your immune system - Meek, Jennifer (Judy Piatkus Pub. LondonGB, 1998)
Explains how the immune system works. Identifies 18 enemies of the immune system, and lists some of the warning signs of an impaired system. Provides a 6-step plan for maintaining immune power including: using immune boosting food; exercising; thinking positively; and exposure to sunlight. Proposes strategies for immune system repair, and includes an A - Z of natural infection fighters. Provides immune-boosting recipes and lists dietary supplements which strengthen the system.